The Value of Isosulfan Blue Dye in Addition to Isotope Scanning in the Identification of the Sentinel Lymph Node in Breast Cancer Patients With a Positive Lymphoscintigraphy: A Randomized Controlled Trial (ISRCTN98849733). Issue 2 (August 2015) - O'Reilly, Elma Anna; Prichard, Ruth S.; Al Azawi, Dhafir; Aucharaz, Nitin; Kelly, Gabrielle; Evoy, Denis; Geraghty, James; Rothwell, Jane; O'Doherty, Ann; Quinn, Cecily; Skehan, Stephen J.; McDermott, Enda W.
Abstract : Background: Sentinel lymph node biopsy (SLNB) has become the gold standard for axillary staging. Debate remains as to the optimal method of SLN detection. Objectives: Determine whether patients undergoing an SLNB required the addition of isosulfan blue dye to radioisotope when an SLN was identified on a preoperative lymphoscintigram. Methods: A prospective randomized controlled trial comparing the combination of radioisotope and blue dye versus radioisotope alone was performed between March 2010 and September 2012. The trial protocol was registered with Current Controlled Trials. Women with clinically and radiologically node-negative breast cancer with a positive preoperative lymphoscintigram were eligible for inclusion. Results: A total of 667 patients were included in the analysis with 342 patients receiving the combination (blue dye and radioisotope) and 325 patients receiving radioisotope alone. The groups were evenly matched both demographically and pathologically. The mean age was 48 years (48.3 vs 47.7 years; P = 0.47), the mean tumour size was 24.2 mm (24.3 mm vs 24.1 mm; P = 0.7) and there was no statistically significant difference in the grade of the tumors between the 2 groups ( P = 0.58). There was no difference in the identification rate, nor was that in the number of nodes retrieved between the 2 groups ( P = 0.30). There was no difference in the number of positive lymph nodes that were identified between the 2 groups (23.8% vs 22.1%; P = 0.64). Conclusions: This study failed to demonstrate an advantage with the addition of isosulfan blue dye to radioisotope in the identification of the SLN in the presence of a positive preoperative lymphoscintigram. Abstract : The sentinel lymph node biopsy is the gold standard for axillary staging in lymph node–negative patients. However, controversy remains as to the optimal method of sentinel lymph node identification. This randomized controlled trial determines whether isosulfan blue dye with radioisotope improves SNB detection with a positive preoperative lymphoscintigram.